Iso Standards suggestion for physical disability kids’ clothes - Alshaikh, Basmah Abdulmohsen Omran (Journal of Humanities & Social Sciences, 2021)
This research deals with codifying specific standards for clothing of children with mobility disabilities, and how quality standards can be set for them in accordance with their special needs and the possibility of developing quality standards for this type of clothing for this category with the aim of identifying the characteristics of clothing for children with mobility disabilities and analyzing their problems while identifying their clothing needs and then setting the quality standards that contribute, in one way or another, to making clothes for this group, and the research has concluded in its results that the clothes of children with mobility disabilities need certain requirements and accordingly standards are set.